Benefits of HyFlex learning in creating a positive students’ experience - Bohatyrets, Valentyna (Mediaforum : Analytics, Forecasts, Information Management, 2020)
During the COVID-19 pandemic, HyFlex teaching/learning has increasingly grown into a crucial feature of education. My strong conviction is the integration of information technology in education will be further accelerated and online education has eventually become an integral component of present-day education. Despite the drawbacks, there are some obvious benefits to leveraging a HyFlex course model. It allows students more flexibility than ever before, meaning they can adjust and adapt as needed to accommodate their schedules (in our case, being in Ukraine or abroad). It also gives students access to a greater breadth of learning materials than they would otherwise receive. It is worth mentioning that after Covid-19 the world and education have changed dramatically, with the distinctive rise of e-learning, whereby teaching is undertaken remotely and on digital platforms. This resulted in the largest “online movement” in the history of education. Importantly, research suggests that online learning has been shown to increase retention of information and be less time-consuming, which means the changes Coronavirus have caused will be here to stay.
Переваги змішаного навчання у процесі створення сприятливих умов для навчання студентів
Keywords: HyFlex teaching/learning; students; Covid-19; flexibility; adaptability; positive experience,; hybrid online course